Pinjaman Online Dalam Perspektif Hukum Islam - Amelia, Rizqa; Harahap, Muhammad Farhan; Darma, Surya (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
With the rapid development of information technology, various online applications have emerged to make it easier to borrow money online, but many still don't know whether this is prohibited for religious reasons or not. The need for financing or working capital attracts borrowers to use online loan services. Therefore, the authors deem it necessary to conduct this research, the purpose of which is to analyze the legality of online credit from the perspective of Islamic law. This study uses a qualitative descriptive method and the type of research is library research, which collects data or papers related to Islamic contractual law which are of a literary nature. the method used is a descriptive approach where the author describes the law of qiradh in fiqh muamalah and the data sources obtained from various fiqh books. Online loans, also known as fintech (financial technology), are financial services in the form of loans whose applications use information technology, internet networks and contracts where lenders and borrowers do not meet face to face. The results of this study show that in Islamic law online loans are permissible, based on the principle of mu'amalah, namely basically all forms of mu'amalah are permissible. Apart from what is prohibited in the Al-Qur'an and As-Sunnah and Fatwa of the National Sharia Council No. 117/DSN-MUI/IX/2018 states that online loans are permissible, most importantly not against Sharia with the principles of usury, gharar, maysir, tadlis, dharar, zhulm and haram.